2016
DOI: 10.1080/15374416.2015.1121824
|View full text |Cite
|
Sign up to set email alerts
|

Can’t Take My Eyes Off of You: Eye Tracking Reveals How Ruminating Young Adolescents Get Stuck

Abstract: Rumination, a cognitive process that involves passively, repetitively focusing on negative feelings and their meaning, is a transdiagnostic risk factor for psychopathology. Research with adults has suggested that attentional control difficulties may underlie rumination, but questions remain about the nature of these processes. Furthermore, the relationship between attentional control and rumination in youth has received little empirical examination. In the present study, 92 youth (ages 9–14; 72% girls; 74% Cau… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 57 publications
2
14
1
Order By: Relevance
“…Relatively few studies have examined rumination in relation to cognitive control processes or negative emotional biases in youth. In line with evidence from adults, behavioral studies in late childhood and adolescence have found that high trait rumination is associated with difficulty inhibiting responses to negatively valenced stimuli, particularly when switching from negative to positive blocks in an emotional Go/NoGo task (Hilt, Leitzke, & Pollak, 2014) and with longer gaze-time to negative faces in an emotional dot-probe task (Hilt, Leitzke, & Pollak, 2017). Further, Wagner, Alloy, and Abramson (2015) found that, in adolescent boys with elevated depressive symptoms, rumination predicted worse sustained attention on a counting task.…”
Section: Rumination In Youthsupporting
confidence: 52%
“…Relatively few studies have examined rumination in relation to cognitive control processes or negative emotional biases in youth. In line with evidence from adults, behavioral studies in late childhood and adolescence have found that high trait rumination is associated with difficulty inhibiting responses to negatively valenced stimuli, particularly when switching from negative to positive blocks in an emotional Go/NoGo task (Hilt, Leitzke, & Pollak, 2014) and with longer gaze-time to negative faces in an emotional dot-probe task (Hilt, Leitzke, & Pollak, 2017). Further, Wagner, Alloy, and Abramson (2015) found that, in adolescent boys with elevated depressive symptoms, rumination predicted worse sustained attention on a counting task.…”
Section: Rumination In Youthsupporting
confidence: 52%
“…Moreover, difficulties disengaging attention from negative stimuli are associated with heightened emotional reactivity in response to negative mood and stress induction in adults (Compton, Heller, Banich, Palmieri, & Miller, 2000; Sanchez et al, 2013), whereas stronger switching abilities are associated with more effective emotion regulation (i.e., downregulation of negative affect) in response to a negative mood induction (Malooly, Genet, & Siemer, 2013). In two recent studies of youth, difficulty inhibiting negative emotional information on a switching task (Hilt, Leitzke, & Pollak, 2014) and difficulty disengaging attention from emotional stimuli (Hilt, Leitzke, & Pollak, in press) were associated with trait depressive rumination. Providing more direct support for the idea that strong attentional control may diminish stress reactivity, cognitive bias training studies reveal that teaching individuals to disengage their attention from negative stimuli and to increase cognitive control reduces rumination (Siegle et al, 2014; Siegle et al, 2007) and reactivity to stressful events (for a review, see Joormann & Vanderlind, 2014).…”
Section: Attentional Control Deficits As a Predictor Of Heightened Stmentioning
confidence: 99%
“…Only a handful of studies have utilized eye-tracking measures with dot-probe paradigms to examine AB in youth (Burris, Barry-Anwar, & Rivera, 2017; Burris, Barry-Anwar, Sims, et al, 2017; Hilt, Leitzke, & Pollak, 2017; Price et al, 2013, 2016; Tsypes, Owens, & Gibb, 2017). These studies commonly measured (a) initial attention vigilance to emotional faces (e.g., angry face; e.g., Price et al, 2016; Tsypes et al, 2017); and (b) sustained attention preference toward the emotional faces (e.g., Hilt et al, 2017). These indices showed improved internal consistency and reliability compared to RT measures in 9- to 13-year-olds (Price et al, 2015).…”
Section: Multimodal Approaches Facilitate the Delineation Of Attentiomentioning
confidence: 99%
“…These indices showed improved internal consistency and reliability compared to RT measures in 9- to 13-year-olds (Price et al, 2015). Findings from three studies that compared dot-probe eye-tracking and RT indices showed that while eye-tracking measures were associated with levels of rumination (Hilt et al, 2017), suicidal ideation (Tsypes et al, 2017), and transition from anxiety to later depression (Price et al, 2016). Eye-tracking findings were evident even when there were no symptom-related differences in RT scores.…”
Section: Multimodal Approaches Facilitate the Delineation Of Attentiomentioning
confidence: 99%